(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of this work is to reduce mutual coupling by incorporating circular CSRR into metamaterial structures. Mutual coupling values are measured for different frequencies and the values are compared with the antenna array without the metamaterial structures. Materials And Methods: Mutual coupling in circular-shaped CSRR metamaterial is compared with that of antenna array without metamaterial. Each group has 10 samples. The mutual coupling values are measured by varying the operating frequency. The G power calculation is 0.8. Results: The experimental results indicate a reduced mutual coupling using the circular-shaped CSRR metamaterial in the two element antenna array compared with the non-metamaterial array. The mean mutual coupling in circular CSRR is -14.36 and in the non-metamaterial antenna array, it is -8.73 with the significance p = 0.023. Conclusion: The circular-shaped CSRR metamaterial structure in the two element antenna array exhibits a better reduction in mutual coupling compared to the antenna array without the metamaterial structure.